Enhancing MSME Performance: Optimizing Work Engagement and Knowledge Sharing - Suseno, Bambang (Journal of Economics and Business (JECOMBI), 2025)
Micro, small, and medium enterprises (MSMEs) play a crucial role in economic growth and job creation. However, their performance is often constrained by internal challenges, particularly in areas such as work engagement and knowledge sharing. While previous research has recognized the importance of these factors in business success, their combined impact on MSME performance remains underexplored, especially in developing economies like Indonesia. This study aims to address this gap by examining the extent to which work engagement and knowledge sharing influence MSME performance. A quantitative research design was employed, collecting data from 90 MSME owners in Medan City. The hypothesis testing results confirm that work engagement and knowledge sharing both have a significant positive effect on MSME performance. Businesses with high owner engagement and active knowledge sharing exhibit higher operational efficiency and improved decision-making, leading to superior overall performance. However, the findings also highlight key barriers such as limited communication infrastructure, lack of trust, and leadership constraints, which may hinder the effective implementation of these factors. To overcome these challenges, MSMEs should foster an inclusive work environment, invest in employee development, and leverage digital tools for knowledge sharing. This study provides valuable insights for MSME owners and policymakers to enhance business sustainability through better engagement and collaboration. Future research should explore the moderating role of digital transformation and leadership styles in strengthening the relationship between work engagement, knowledge sharing, and MSME performance.